Estimate the Rate of Change in Forest Cover and Its Impact on Soil by Using GIS And Remote Sensing, A Case Study of Gadchiroli District, Maharashtra - Medhe Ravindra Sampat; Madhe Ganesh Kashinath; Gadekar Deepak Janardhan (The Bioscan, 2024)
The forest is an essential aspect of the environment. It contributes significantly to the nation's economic, social, and environmental well-being. However, deforestation, population growth, unscientific urbanisation, rising trend of industrialisation, increasing mining activities, agricultural land use, shifting cultivation, and effects on soil, water, and biodiversity resulting from unsustainable human activities, among others, pose a severe threat to these forests. As a result, it is critical to develop policies that promote sustainable forest management, prevent desertification, halt and reverse land degradation, and halt biodiversity loss. Because of satellite remote sensing, humans have been able to monitor and gather information about the Earth's surface at many spatial and temporal scales. Within the Gadchiroli district of Maharashtra state, India, this project aims to determine the forest cover change and detect the spatiotemporal altering paradigms of the forest. Using Landsat 5 and Landsat 8 data with 30 m spatial resolution, various indices such as Normalized Difference Vegetation Index, Enhanced Vegetation Index, and Bare Soil Index Scaled Shadow Index were utilised to highlight the geographical pattern of Forest cover change detection. Several multi-temporal data (1989, 2004 and 2019) were employed to show the change in forest cover in the research area. The results demonstrate that between 1989 and 2019, the forest crown cover decreased. It is also said that throughout 30 years (1998 – 2009), 933 km2 of land was degraded. During the study period (1989 – 2019), it was noticed that highly thick forest areas decreased over time, whereas non-forest areas expanded continuously.